PENGGUNAAN KEKERASAN DAN SENJATA API OLEH APARAT KEPOLISIAN NEGARA REPUBLIK INDONESIA DALAM PENGAMANAN UNJUK RASA - , RISKA RETY, Prof. Dr. Marcus Priyo Gunarto, S.H., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Kepolisian Negara Republik Indonesia (Polri) is one institution that is authorized and responsibility to use violence and firearms to support tasks and functions to keep safety and peace in the society. This study aims to explain on the extent of use of force and firearms by the Kepolisian Negara Republik Indonesia officers can do and how its criminal responsibility in securing demonstration. Research method which is used empirical normative using primary data and secondary data. Primary data and secondary data is processed to answer the problem by using descriptive analysis. Sampling techniques used non-random sampling. Type of sampling conducted by purposive sampling, which took testimony through interviews with specific people based on qualifications of the research that has been defined previously. The result of the study showed that the implementation of the use of force and firearms by the Kepolisian Negara Republik Indonesia (Polri) in securing the protests influenced by several factors: an indication of the cause of the protests that grew into mass riots in Indonesia, including law enforcement factors on perceptions of police officers on human rights humans (HAM) in securing the rally, police policy factor in securing the rally, influence the pattern of character building member of the Police, the Police action in protest security, network cooperation and negotiations undertaken in the police handling of the protests and the constraints faced by the police in securing demonstrations, as well as cultural factors (culture) community. Resposibility of Criminals liability for police officers for mis use of force and firearms in securing the rally can be determined based offenses arising from the misuse of force and firearms by police in securing justice protests to general mechanism to determine which form of criminal liability and criminal sanctions violence abuse and firearms by police to securing demonstration.